Sociological and Cultural in the Term of Ancient Arab Criticism - Hashem, Ahmed Mohamed (Thi Qar Arts Journal, 2022)
The research seeks to answer some questions related to the formulation of the term old literary criticism, by examining two influential factors among many factors, namely: (sociological and cultural), and focuses on the literary critic’s dealing with the influences of the society in which he lives and his environment on the one hand, and the influence of Society and its culture in the thought of the critic on the other hand, which made there is a strong relationship between the term criticism and the culture of the Arab society in which the term was born, and this relationship is mediated by the critic, on the grounds that the latter is a person who is affected by the environment in which he lives and is influenced - in one way or another - by the work he creates. Especially the term literary criticism. formulation of the term, sociological, cultural, critical thought